A review on targeted temperature management for cardiac arrest and traumatic brain injury - Ito, Hiroshi; Hosomi, Sanae; Nishida, Takeshi; Nakamura, Youhei; Iba, Jiro; Ogura, Hiroshi; Oda, Jun (Frontiers in Neuroscience, 2024)
Therapeutic hypothermia inhibits organ damage by suppressing metabolism, which makes it a therapy of choice for treating various diseases. Specifically, it is often used to treat conditions involving central nervous system disorders where it is expected to positively impact functional prognosis. Although keeping the body temperature at a hypothermic level has been conventionally used, how to manage the body temperature correctly remains a topic of debate. Recently, the concept of temperature management has been proposed to improve the quality of body temperature control and avoid hyperthermia. This review focuses on the effect of temperature on the central nervous system in conditions involving central nervous system disorders and the practice of temperature management in clinical situations.